Vaginal breech delivery seen from a different perspective - a case series - Fonseca,Andreia (2019)
Term breech presentation is a common indication for cesarean delivery. However, concern over the implications of planned cesareans on maternal morbidity and complications for future pregnancies as well as the limitations attributed to the Term Breech Trial have shed new light on the vaginal breech delivery, with different approaches being attempted. We report three cases of term vaginal breech delivery in the upright position, one of them requiring Pipers forceps for fetal head delivery. No other relevant complications occurred. As with deliveries in lithotomy position, clinical expertise and case selection are prerequisites for favorable maternal and neonatal outcomes.